The Effect of Handgrip and Resistance Band Training on The Accuracy Ability of Table Tennis Forehand Drive Seen From the Speed Of Hand Reaction - Ibrahim, Yusril; Hasan, Muh. Said; Nawir, Nukhrawi; Hudain, Muh. Adnan; Jamaluddin, Jamaluddin (UNIVERSITAS NEGERI MAKASSAR, 2024)
This study aims to determine the effect of Handgrip Exercise and resistance band exercise and hand reaction speed and the interaction of both on the accuracy of forehand driveability in FIKK UNM students. This study was conducted using a field experiment method through Handgrip Exercise and resistance band exercise in FIKK UNM students. The sample was obtained through a random sampling technique, namely, respondents were selected using a lottery system. From the lottery system, 40 samples were obtained into the Handgrip Exercise group, 20 samples, and the Resistance Exercise group, 20 samples. The data generated from the test and measurement were analyzed using Two Ways Anova with the help of SPSS 22.00. From the results of Two Ways Anova, it can be proven that: 1. There is a difference in the effect of Handgrip training and resistance band training on the accuracy of Forehand drive table tennis in FIKK UNM students., 2. There is a difference in the effect of high hand reaction speed and low hand reaction speed on the accuracy of Forehand drive table tennis in FIKK UNM students., 3. There is an interaction between Handgrip training, resistance band training, and hand reaction speed on the accuracy of Forehand drive table tennis in FIKK UNM students., 4. There is a difference in the accuracy of Forehand drive table tennis between high hand reaction speed using Handgrip training and resistance band training in FIKK UNM students., 5. There is a difference in the accuracy of Forehand drive table tennis between low hand reaction speed using Handgrip training and resistance band training in FIKK UNM students.